2016
DOI: 10.1007/s12298-016-0365-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of some biochemical parameters of argan pulp morphotypes (Argania spinosa (L) Skeels) during maturity and according to the continentality in Essaouira region (Morocco)

Abstract: Argania spinosa (L.) Skeels is an endemic forest tree for Morocco. The phytochemical compounds evaluation of four different morphotypes of their fruit pulps was investigated. The total content of sugar, protein and phenolic compounds were monitored during three different stages of maturation in the semi-continental (Mejji) and littoral regions (R'zwa). Total sugars, proteins, phenolics increased up to the ripe stage of all argan fruit morphotypes in the two regions. Spherical shape had higher sugar and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Based on their results, the total sugar, reducing sugar, and phenolic compounds were 358.28–668.38 mg/g DW, 121.99–267.89 mg/g DW, and 74.37–101.24 mg EGA/g DW, respectively. Additionally, Zhar, et al [ 36 ] reported that the argan pulp spherical morphotype is very rich in sugar (85.5–353.33 mg/g FW) and the phenolic content became significant with the maturation for all fruit morphotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their results, the total sugar, reducing sugar, and phenolic compounds were 358.28–668.38 mg/g DW, 121.99–267.89 mg/g DW, and 74.37–101.24 mg EGA/g DW, respectively. Additionally, Zhar, et al [ 36 ] reported that the argan pulp spherical morphotype is very rich in sugar (85.5–353.33 mg/g FW) and the phenolic content became significant with the maturation for all fruit morphotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the maturation stage of argan fruits influenced significantly all biochemical compounds, and the maturation degree was positively and strongly correlated with all phytochemical compounds. In addition, the region had a significant effect on total protein (Zhar et al, 2016). The total proteins of all morphotypic argan fruit increased significantly and gradually from the green to the ripe stage (Zhar et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Sucrose, fructose, and glucose are reducing sugars produced by photosynthesis, which are important roles in regulating intracellular pressure, plant-water relations, transportation photoassimilates as well as protecting cellular membranes (Stitt et al, 2007). Zhar et al (2016) stated that the total sugar content of argan fruits with different morphotypes at different ripening stages in semi-continental and littoral regions shows significant variation. Generally, the ripe stage for all morphotypes is characterized by the greatest total sugar content values.…”
Section: Discussionmentioning
confidence: 99%
“…The fruits generally ripen between June and August, depending on the location and environmental conditions. The fruits of the argan tree exhibit various phenotypes ( Bani-Aameur et al, 1999 ; Bani-Aameur and Ferradous, 2001 ; Ait Aabd et al, 2011 , 2012 ; Zhar et al, 2016 ), being false drupes (according to Rammal et al, 2009 ) of size ranging from olive to walnut with different morphotypes (oval, rounded, and fusiform). The fruit of A. spinosa is very special; there is a hard stone (seed) under the fleshy pulp with 2–3 (or even 4 or 5) cavities containing false almonds (nuts).…”
Section: Botanical Genetic and Biotechnological Aspectsmentioning
confidence: 99%